2015
DOI: 10.3109/00207454.2015.1010200
|View full text |Cite
|
Sign up to set email alerts
|

TNF-a(-238G/A and -308G/A) gene polymorphisms may not contribute to the risk of ischemic stroke

Abstract: The TNF-a (-238G/A and -308G/A) gene polymorphisms may not be a susceptible predictor of ischemic stroke in Chinese populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…In agreement with the results, a clinical study to evaluate biomarkers for patients at increased risk of stroke did not observe any changes of TNF-α in symptomatic patients with unstable plaques and high-grade carotid artery stenosis compared with asymptomatic patients with stable plaques 47. Furthermore, a very recent investigation on 619 ischemic stroke patients and 612 controls indicated that TNF-α gene polymorphisms may not contribute to the risk of ischemic stroke 48. One study even got opposite results and concluded that exercise-induced TNF-α markedly decreased blood–brain barrier dysfunction in stroke,49 although others still supported the pro-inflammatory role of TNF-α that can exacerbate tissue damage in stroke 18,50.…”
Section: Discussionsupporting
confidence: 83%
“…In agreement with the results, a clinical study to evaluate biomarkers for patients at increased risk of stroke did not observe any changes of TNF-α in symptomatic patients with unstable plaques and high-grade carotid artery stenosis compared with asymptomatic patients with stable plaques 47. Furthermore, a very recent investigation on 619 ischemic stroke patients and 612 controls indicated that TNF-α gene polymorphisms may not contribute to the risk of ischemic stroke 48. One study even got opposite results and concluded that exercise-induced TNF-α markedly decreased blood–brain barrier dysfunction in stroke,49 although others still supported the pro-inflammatory role of TNF-α that can exacerbate tissue damage in stroke 18,50.…”
Section: Discussionsupporting
confidence: 83%
“… 29 The TNF-a -308G/A polymorphism could increase TNF-a expression, which is associated with various inflammatory diseases. 30 , 31 Increasing numbers of scholars are exploring scholars the relationship between TNF-a -308G/A polymorphism and EH, but the conclusions are not consistent.18-26 A single study may not draw a comprehensive and reliable conclusion due to the low effectiveness of the tests used. In addition, because of the different frequencies (TNF-a -308G/A) of the different regions and ethnic groups, the extrapolation of the foreign research is limited.…”
Section: Discussionmentioning
confidence: 99%
“…All 18 studies (with 8075 patients and 8217 controls) assessed TNFa-308G/A (Balding, et al, 2004;Lee, et al, 2004;Um and Kim, 2004;Rubattu, et al, 2005;Harcos, et al, 2006;Lalouschek, et al, 2006;Llamas Sillero, et al, 2007;Banerjee, et al, 2008;Kim, et al, 2010;Tong, et al, 2010;Sultana, et al, 2011;Szabó and Acsády, 2011;Cui, et al, 2012;Tuttolomondo, et al, 2012b;Zhao, et al, 2012;Wawrzynek, et al, 2014;Gu, et al, 2015;Kumar, et al, 2016), while 7 of the 18 studies (with 6039 patients and 5519 controls) examined TNFa-238G/A (Lalouschek et al, 2006;Llamas Sillero et al, 2007;Kim et al, 2010;Tong et al, 2010;Cui et al, 2012;Zhao et al, 2012;Gu et al, 2015).…”
Section: Study Characteristicsmentioning
confidence: 98%